2016
DOI: 10.4025/actascianimsci.v38i4.31498
|View full text |Cite
|
Sign up to set email alerts
|

<b>Black pepper (<i>Piper nigrum</i>) in diets for laying hens on performance, egg quality and blood biochemical parameters

Abstract: The objective of this study was to evaluate the increasing levels (0, 0.1, 0.2, 0.3, 0.4, 0.5 and 0.6%) of black pepper in diets for laying hens on performance, egg quality and blood biochemical parameters. Hissex White hens (n=168) at 30 weeks of age were used. The experimental method was completely randomized with seven treatments with four replicates of six birds each. Estimates of black pepper levels were determined by polynomial regression. The performance showed no significant differences (p > 0.05). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
1
3
2
Order By: Relevance
“…These findings are comparable to those of Liu et al (2020), who found that turmeric had a favorable effect on boosting HDL levels, and Elnaggar et al (2021), who reported that a combination diet of turmeric and black pepper produces better effects than either turmeric or black pepper individually. The effect of D1 (1 % black pepper) on TC or Total Cholesterol level is superior to Melo et al (2016) and Sidhu et al (2017). The results of the LDL levels indicated a substantial (p<0.05) decrease due to the incorporation of the D1 and D4 diet in the egg yolk are reported to be similar to those of Elnagger et al (2021).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These findings are comparable to those of Liu et al (2020), who found that turmeric had a favorable effect on boosting HDL levels, and Elnaggar et al (2021), who reported that a combination diet of turmeric and black pepper produces better effects than either turmeric or black pepper individually. The effect of D1 (1 % black pepper) on TC or Total Cholesterol level is superior to Melo et al (2016) and Sidhu et al (2017). The results of the LDL levels indicated a substantial (p<0.05) decrease due to the incorporation of the D1 and D4 diet in the egg yolk are reported to be similar to those of Elnagger et al (2021).…”
Section: Resultssupporting
confidence: 77%
“…The enhanced eggshell quality is due to increased laying bird feed intake, which releases serum calcium from plasma protein, allowing more Ca2+ from the blood to be involved in the production of eggshells, and our findings are superior to those of Liu et al (2020). Melo et al (2016), reported that black pepper improves egg quality, and our findings with black pepper inclusion were superior to their findings. In the current study, the egg shape index of laying hens fed with D1 (1 % black pepper) was greater than the other experimental groups, which is similar to Bugdayci et al (2018).…”
Section: Resultscontrasting
confidence: 44%
“…(2013) reported that dietary inclusion of black cumin seed at the levels of 10 to 15, 30 and 30 to 50 g/kg, respectively, increased egg weights. Furthermore, Melo et al. (2016) reported no significant differences in egg weight between control and black pepper supplemented groups.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, it was identified that piperine has massive advantages over other natural products: it produces no residues in the animal meat, increases cell recovery, and promotes anti-apoptotic and anti-oxidative activities. This suggests that piperine could be beneficial when used in the event of a compromised immune system, which is usually treated with antibiotics [19,20]. …”
Section: Introductionmentioning
confidence: 99%